Vibration response of the polar supply and research vessel the S. A. Agulhas II in Antarctica and the Southern ocean - Soal, Keith Ian (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.